2020
DOI: 10.3390/ijms21041502
|View full text |Cite
|
Sign up to set email alerts
|

ERM Proteins at the Crossroad of Leukocyte Polarization, Migration and Intercellular Adhesion

Abstract: Ezrin, radixin and moesin proteins (ERMs) are plasma membrane (PM) organizers that link the actin cytoskeleton to the cytoplasmic tail of transmembrane proteins, many of which are adhesion receptors, in order to regulate the formation of F-actin-based structures (e.g., microspikes and microvilli). ERMs also effect transmission of signals from the PM into the cell, an action mainly exerted through the compartmentalized activation of the small Rho GTPases Rho, Rac and Cdc42. Ezrin and moesin are the ERMs more hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 153 publications
2
41
0
Order By: Relevance
“…Chemokines induce transient ERMs de-phosphorylation, dissociation from the plasma membrane and the actin cytoskeleton, and release of GEF proteins that in turn activate Rac1 and Cdc42. This supports F-actin polymerization at the protrusive leading edge (Hao et al, 2009;Garcia-Ortiz and Serrador, 2020). Then, RhoA-dependent re-phosphorylation of ERMs induces their selective segregation to the uropod, where they recruit adhesion molecules, such as ICAM-1, -2, -3, CD44, and PSGL-1 (Figure 3).…”
Section: Cytoskeleton Rearrangements Shaping T Cell Polarizationmentioning
confidence: 72%
See 1 more Smart Citation
“…Chemokines induce transient ERMs de-phosphorylation, dissociation from the plasma membrane and the actin cytoskeleton, and release of GEF proteins that in turn activate Rac1 and Cdc42. This supports F-actin polymerization at the protrusive leading edge (Hao et al, 2009;Garcia-Ortiz and Serrador, 2020). Then, RhoA-dependent re-phosphorylation of ERMs induces their selective segregation to the uropod, where they recruit adhesion molecules, such as ICAM-1, -2, -3, CD44, and PSGL-1 (Figure 3).…”
Section: Cytoskeleton Rearrangements Shaping T Cell Polarizationmentioning
confidence: 72%
“…Various pivotal proteins facilitate the interplay between membrane, cytoskeletal, and organelle components. Among them, membrane-cytoskeleton linkers, such as the ezrin-radixin-moesin (ERM) family of proteins, talin, and several polarity regulators, play important roles at the different stages of T cell migration and immunological synapse formation (Krummel and Macara, 2006;Lasserre and Alcover, 2010;Garcia-Ortiz and Serrador, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ezrin is a scaffold protein that promotes protein interactions with the actin cytoskeleton to regulate cell migration. 66,67 Especially in PCa, ezrin can connect the tail of the βsubunit in αvβ3 to actin. [68][69][70] In experiments assessing how CXCL16 affects PCa invasion, researchers found that treatment of PC3 cells with CXCL16 cause αvβ3 molecules to cluster together on the cell surface, and p-Ezrin and F-Actin levels were increased significantly.…”
Section: Cellular Chemokines Can Enhance Pca Invasion By Regulating αmentioning
confidence: 99%
“…We noticed in resting T cells a reduction in the concentration of Arpc1b (group II) and a lack of an up-regulation of Arpc4 (group VI), in activated T cells, representing two of the five essential and non-interchangeable components of the Arp2/3 complex which promotes filamentous (F) actin branching (see Figure 3c) (Goley & Welch, 2006). The organizer proteins Moesin (Msn) and Ezrin (Ezr) (Group III) that link F-actin to the plasma membrane, remained highly expressed in stimulated CCT8 T-/-T cells thus impairing the remodeling of the cytoskeleton upon activation (Garcia-Ortiz & Serrador, 2020). Furthermore, several proteins failed to be reduced in response to CD4 + T cell activation (group III) including Ifit1, a protein expressed in response to interferons and the subsequent recruitment of STAT1 that also negatively regulates pro-inflammatory genes (John, Sun et al, 2018).…”
Section: The Lack Of Cct8 Compromises Proteostasis In Both Resting Anmentioning
confidence: 99%